Cytotoxic triterpenoids from the stem bark of Aglaia angustifolia. Issue 8 (15th July 2021) - Hutagaol, Ricson Pemimpin; Harneti, Desi; Safari, Agus; Hidayat, Ace Tatang; Supratman, Unang; Awang, Khalijah; Shiono, Yoshihito
Abstract: A seco-apotirucallane-type triterpenoid, namely angustifolianin (1 ), along with three dammarane-type triterpenoids, (20 S, 24 S )-epoxy-dammarane-3β, 25-diol (2 ), 3-epi-cabraleahydroxylactone (3 ), and cabralealactone (4 ), were isolated from the stem bark of Aglaia angustifolia Miq. The Chemical structure of the new compounds was elucidated on the basis of spectroscopic data. All of the compounds were evaluated for their cytotoxic effects against MCF-7 breast cancer cells. Among those compounds, angustifolianin (1) showed strongest cytotoxic activity with an IC50 value of 50.5 μg/ml.